Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1021/mp100273t
|View full text |Cite
|
Sign up to set email alerts
|

Superparamagnetic Iron Oxide Nanotheranostics for Targeted Cancer Cell Imaging and pH-Dependent Intracellular Drug Release

Abstract: Purpose-To develop antibody-and fluorescence-labeled superparamagnetic iron oxide nanoparticle (SPIO) "nanotheranostics" for magnetic resonance imaging (MRI) and fluorescence imaging of cancer cells and pH-dependent intracellular drug release.Method-SPIO nanoparticles (10 nm) were coated with amphiphilic polymers and PEGylated. The antibody HuCC49ΔCH2 and fluorescent dye 5-FAM were conjugated to the PEG of IONPs. Anticancer drugs doxorubicin (Dox), and azido-doxorubicin (Adox), MI-219, 17-DMAG containing prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(75 citation statements)
references
References 39 publications
1
74
0
Order By: Relevance
“…Targeted nanocarriers exhibited IC 50 value of 0.44 M which was significantly lower than that of the non-targeted nanocarriers (1.42 M). 104 …”
Section: Targeted Theranostic Nanocarriers Providing Dual Modal Imagimentioning
confidence: 99%
“…Targeted nanocarriers exhibited IC 50 value of 0.44 M which was significantly lower than that of the non-targeted nanocarriers (1.42 M). 104 …”
Section: Targeted Theranostic Nanocarriers Providing Dual Modal Imagimentioning
confidence: 99%
“…DOX was then conjugated to the Fe 3 O 4 colloidal nanocrystal clusters through a hydrazone bond to provide a pH-sensitive drug release capability, and the release rate of DOX was dramatically improved in low pH environments, whereas almost no DOX was released at neutral pH values. Zou et al [91] prepared superparamagnetic iron oxide nanoparticles (SPIO, 10 nm) coated with amphiphilic polymers and PEGylated. The antibody HuCC49DCH 2 and fluorescent dye 5-FAM were conjugated to the PEG on iron oxide nanoparticles, and the anticancer drugs DOX, azido-doxorubicin (Adox), MI-219, and 17-DMAG, which contain primary amine, azide, secondary amine, and tertiary amine, respectively, were encapsulated into the iron oxide nanoparticles.…”
Section: Inorganic/organic-composite Ph-responsive Drug-delivery Systemsmentioning
confidence: 99%
“…Therapeutic agents that contain amine groups have demonstrated pH-dependent release; hypothesized to be a result of the amine group protonation 10 . Zou et al 10 recently reported the development of a novel antibody- and fluorescence-labeled superparamagnetic iron oxide nanoparticle (SPIO) nanotheranostic carrier for MRI and fluorescent imaging, and pH-dependent intracellular drug release. To create a dual-imaging particle, the group conjugated the fluorescent dye 5-FAM to the PEG polymer coating iron oxide nanoparticles (IONPs).…”
Section: Responsive Carriers Systemsmentioning
confidence: 99%